Premolar enamel thickness and distribution of a Miocene hominid Lufengpithecus hudienensis compared with Pleistocene and extant hominids. Issue 157 (August 2021) - Pan, Lei; Ji, Xueping; Liao, Wei; Wang, Wei; Liu, Jianhui; Xing, Song
Abstract: Lufengpithecus hudienensis is a Late-Miocene hominid from the Yuanmou basin of southwestern China. Previous studies link Lufengpithecus to either the Sivapithecus -orangutan clade or a derived branch from the basal stem of the Hominidae. Despite a rich fossil assemblage, the taxonomy of L. hudienensis and its phylogenetic relationship with other hominids is still unclear. Enamel thickness in fossil and modern hominids can provide insights into taxonomy, phylogeny, and dietary reconstructions. In this study, 24 upper and lower L. hudienensis premolars were imaged using high-resolution microcomputed tomography. Three-dimensional average enamel thickness and relative enamel thickness (RET) indices, as well as whole-crown enamel distribution patterns were recorded for the L. hudienensis specimens and compared with a total of 113 specimens of fossil and extant apes and recent modern humans (RMH): fossil Pongo ( n = 36), Gigantopithecus blacki ( n = 21), Pan troglodytes ( n = 11), Gorilla gorilla ( n = 7), and RMH ( n = 38). RET of the premolars of L. hudienensis was found to be similar to that of fossil Pongo, P. troglodytes, and G. gorilla, but less than Gi. blacki and RMH values. The distribution of enamel thickness shows a taxon-specific pattern for L. hudienensis, generally characterized by thicker enamel on the lateral wall than on the cusp apex, on the lingual cusp of the upper and buccal cusp of the lower premolars, with some differences with respect to fossil Pongo, Gi. blacki, P. troglodytes, and G. gorilla patterns. Additional characterizations of enamel thickness distribution patterns of the molars and other dental endostructural morphologies are needed to further explore the phylogenetic relationships of L. hudienensis with other hominids.